Meningkatkan Hasil Belajar Pendidikan Agama Katolik dan Budi Pekerti Materi Aku Pribadi yang Unik Model Problem Based Learning (PBL) Berbantuan Audio Visual untuk Kelas X SMAS Karya Sedar Biru-Biru 2024/2025 - Julista Br Tarigan; YL. Sukestiyarno; Martina Murliani (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research was conducted at SMAS Karya Sedar Biru-Biru in Class X with the subjects of this study were 10 students. Based on the analysis of data on the initial reflection which still showed that the learning outcomes of students were still lacking, the research was conducted by implementing the Problem Based Learning (PBL) learning model in learning Unique Personal Humans to improve student learning outcomes. 1) The formulation of the problem in this study is: How to improve the learning outcomes of Catholic Religious Education on the material